Antifungal Efficacy of Plant Oils Containing Thymol and Carvacrol in Controlling Botrytis cinerea, the Causal Agent of Grape (Vitis vinifera) GrayMould - M, Zaker; L, Zaker (The Agriculturists, 2018)
The efficacy of a large number of plant extracts and essential oils in controlling plant diseases has been proven worldwide. Botrytis cinerea has attacked a wide host range causing severe loss in the field and at storage. In this study the antifungal efficacy of essential oils of three medicinal plants namely wild marjoram (Zataria multifolia), wild savory (perennial) (Satureja mutica) and savory (annual) (Satureja hortensis) possessing these compounds at three concentrations: 50, 100 and 200 ppm were evaluated in controlling the mycelial growth, spore germination and germ tube elongation of B. cinerea. All treatments except savory (annual) essential oil at 50 ppm showed significant differences with the control in inhibiting the mycelial growth as well as spore germination and germ tube elongation of B. cinerea (p=0.01). It was also noted that wild marjoram at 100 ppm and wild savory (perennial) essential oils at 200 ppm could completely (100%) inhibit the growth of the fungus. Essential oils from wild marjoram and wild savory had higher antifungal activity than annual savory. Their suitable formulations could be prepared and used as safe alternatives for controlling moulds of horticultural products during storage. The Agriculturists 2018; 16(2) 15-24